Targeted quantitative mass spectrometric immunoassay for human protein variants - Trenchevska, Olgica; Nedelkov, Dobrin (Springer Science and Business Media LLC, 2011)
Post-translational modifications and genetic variations give rise to protein variants that significantly increase the complexity of the human proteome. Modified proteins also play an important role in biological processes. While sandwich immunoassays are routinely used to determine protein concentrations, they are oblivious to protein variants that may serve as biomarkers with better sensitivity and specificity than their wild-type proteins. Mass spectrometry, coupled to immunoaffinity separations, can provide an efficient mean for simultaneous detection and quantification of protein variants.